Identification of microRNAs in skeletal muscle associated with lung cancer cachexia. Issue 2 (11th December 2019) - van de Worp, Wouter R.P.H.; Schols, Annemie M.W.J.; Dingemans, Anne‐Marie C.; Op den Kamp, Céline M.H.; Degens, Juliette H.R.J.; Kelders, Marco C.J.M.; Coort, Susan; Woodruff, Henry C.; Kratassiouk, Gueorqui; Harel‐Bellan, Annick; Theys, Jan; van Helvoort, Ardy; et al.
Abstract: Background: Cachexia, highly prevalent in patients with non‐small cell lung cancer (NSCLC), impairs quality of life and is associated with reduced tolerance and responsiveness to cancer therapy and decreased survival. MicroRNAs (miRNAs) are small non‐coding RNAs that play a central role in post‐transcriptional gene regulation. Changes in intramuscular levels of miRNAs have been implicated in muscle wasting conditions. Here, we aimed to identify miRNAs that are differentially expressed in skeletal muscle of cachectic lung cancer patients to increase our understanding of cachexia and to allow us to probe their potential as therapeutic targets. Methods: A total of 754 unique miRNAs were profiled and analysed in vastus lateralis muscle biopsies of newly diagnosed treatment‐naïve NSCLC patients with cachexia ( n = 8) and age‐matched and sex‐matched healthy controls ( n = 8). miRNA expression analysis was performed using a TaqMan MicroRNA Array. In silico network analysis was performed on all significant differentially expressed miRNAs. Differential expression of the top‐ranked miRNAs was confirmed using reverse transcription–quantitative real‐time PCR in an extended group ( n = 48) consisting of NSCLC patients with ( n = 15) and without cachexia ( n = 11) and healthy controls ( n = 22). Finally, these miRNAs were subjected to univariate and multivariate Cox proportional hazard analysis using overall survival and treatment‐induced toxicity data obtained during the follow‐up of this group of patients. Results: We identified 28 significant differentially expressed miRNAs, of which five miRNAs were up‐regulated and 23 were down‐regulated. In silico miRNA‐target prediction analysis showed 158 functional gene targets, and pathway analysis identified 22 pathways related to the degenerative or regenerative processes of muscle tissue. Subsequently, the expression of six top‐ranked miRNAs was measured in muscle biopsies of the entire patient group. Five miRNAs were detectable with reverse transcription–quantitative real‐time PCR analysis, and their altered expression (expressed as fold change, FC) was confirmed in muscle of cachectic NSCLC patients compared with healthy control subjects: miR‐424‐5p (FC = 4.5), miR‐424‐3p (FC = 12), miR‐450a‐5p (FC = 8.6), miR‐144‐5p (FC = 0.59), and miR‐451a (FC = 0.57). In non‐cachectic NSCLC patients, only miR‐424‐3p was significantly increased (FC = 5.6) compared with control. Although the statistical support was not sufficient to imply these miRNAs as individual predictors of overall survival or treatment‐induced toxicity, when combined in multivariate analysis, miR‐450‐5p and miR‐451a resulted in a significant stratification between short‐term and long‐term survival. Conclusions: We identified differentially expressed miRNAs putatively involved in lung cancer cachexia. These findings call for further studies to investigate the causality of these miRNAs in muscle atrophy and the mechanisms underlying their differential expression in lung cancer cachexia.